BIO-ETHANOL PRODUCTION THROUGH SIMULTANEOUS SACCHARIFICATION AND CO-FERMENTATION (SSCF) OF OXIDATIVE DELIGNIFICATION PRETREATED COTTON BIOMASS - ABIRAMI. M,; GEETHA DEVI. C,; SREEMATHI. T.K,; AARTHI.B,; RAJENDRAN. R,; RAJALAKSHMI.V, (The Bioscan, 2024)
The practice of producing ethanol from cotton waste is an eco-friendly process in biofuel production since it makes use of renewable sources. This research focused on the pretreatment processes and the enzyme applications on cotton waste with the goal of enhancing sugar release from hard waste and grinding waste obtained from textiles in Coimbatore, India. Several pretreatment techniques, such as wet oxidation and liquid hot water pretreatment, were tested for cellulose, hemicellulose, and lignin solubilization. Then cellulase and laccase were utilized in enzymatic hydrolysis in varying ratios, and it was found out that the order of cellulose and then laccase showed the best sugar yields, and the process was performed with Zymomonas mobilis and Candida sp. yeast. Significant ethanol production was obtained from grinding waste compared to hard waste, with a maximum yield of 0.2 grams of ethanol per gram of sample obtained. Ethanol production from the biomass was further characterized by FTIR, where the presence of alcoholic functional groups in the distilled ethanol confirmed the fermentation process. This paper outlines the potential of utilizing cotton waste as a suitable substrate for bioethanol production.